Electron beam induced surface activation: a method for the lithographic fabrication of nanostructures via catalytic processes - Marbach, Hubertus (Applied Physics A-Materials Science & Processing, 2014)
In focused electron beam induced processing (FEBIP), the very narrow electron beam of a scanning electron microscope or transmission electron microscope is used to locally modify matter on the nanometer scale. Recently, the family of FEBIP could be considerably expanded by the technique of focused electron beam induced surface activation (EBISA). In EBISA, the surface itself gets chemically activated by the impact of the electron beam without the presence of precursor molecules. In the second EBISA processing step, the surface is exposed to a precursor molecule which is then catalytically decomposed at the pre-irradiated/activated areas and eventually continues to grow autocatalytically upon prolonged precursor dosage. In this way, electron irradiation and precursor dosage are effectively separated. One of the advantages is that, due to the autocatalytic growth, the size of the corresponding nanostructures can be controlled by the precursor dosage and corresponding electron proximity effects can be omitted. Another advantage is the parallel processing of the pre-irradiated regions during precursor dosage. This bears the potential to significantly reduce the fabrication times for larger deposits compared to the classical electron beam induced deposition approach, in which precursor molecules are sequentially dissociated by the impact of the electron. The fundamentals and apparent further developments as well as the potential and challenges of the comparably new EBISA technique, and more general of catalytic effects in FEBIP are presented and discussed.
EAM Import::2019-03-14